Diagnóstico do uso de softwares educacionais nas escolas de ensino fundamental e médio do Município de Itacoatiara - Jessé Barbosa dos Santos (Universidade Federal do Amazonas, 2016)
The use of computational tools to support the process teaching-learning has motivated several investigations and research project. The insertion of information technology in Education is also seen as a contributing element in the construction of a school focused on reality and promoting human autonomy. Faced with this new educational paradigm, schools should provide the student the efficiency in the construction of knowledge, converting the classroom in a real space of interaction, of exchange of results, adapting the data to the reality of the student. The computer must be inserted into the classroom as a potentializing tool for this development, since this new educational tool, brought a new form of aid in children's learning. Thus we emphasize the importance of using educational tools in the teaching and learning process, either through software specific educational activities or through the creativity of the teachers in using the resources that accompany the computers. With the objective of investigating the use of the information technology, by teachers and students, a survey was carried out educational software (proprietary and free) existing in the public and private primary and secondary schools in the municipality of Itacoatiara, in order to carry out a study demonstration of the application of these resources. Through a questionnaire, applied to those responsible for the school, it was observed that 33% of schools have a laboratory, but that no teacher uses educational tools to assist in the teaching-learning process of its students. In addition, it was found that the internet is available in 67% of the laboratories, and that in three of them, the community has access to computers, at times pre-established by the school management. In order to mitigate this In reality, a list containing software and games was made available. educational activities, together with an evaluation of them with regard to respect to functional and curricular aspects, in order to contribute with improving teaching.